Importance of flagella in acute and chronic Pseudomonas aeruginosa infections - Anne Lorenz; Matthias Preuße; Sebastian Bruchmann; Vinay Pawar; Nora Grahl; Marina C. Pils; Laura M. Nolan; Alain Filloux; Siegfried Weiss; Susanne Häussler (Environmental Microbiology, 2019)
Summary Pseudomonas aeruginosa is an environmental microorganism and a causative agent of diverse acute and chronic, biofilm‐associated infections. Advancing research‐based knowledge on its adaptation to conditions within the human host is bound to reveal novel strategies and targets for therapeutic intervention. Here, we investigated the traits that P. aeruginosa PA14 as well as a virulence attenuated Δ lasR mutant need to survive in selected murine infection models. Experimentally, the genetic programs that the bacteria use to adapt to biofilm‐associated versus acute infections were dissected by passaging transposon mutant libraries through mouse lungs (acute) or mouse tumours (biofilm‐infection). Adaptive metabolic changes of P. aeruginosa were generally required during both infection processes. Counter‐selection against flagella expression was observed during acute lung infections. Obviously, avoidance of flagella‐mediated activation of host immunity is advantageous for the wildtype bacteria. For the Δ lasR mutant, loss of flagella did not confer a selective advantage. Apparently, other pathogenesis mechanisms are active in this virulence attenuated strain. In contrast, the infective process of P. aeruginosa in the chronic biofilm model apparently required expression of flagellin. Together, our findings imply that the host immune reactions against the infectious agent are very decisive for acuteness and duration of the infectious disease. They direct disease outcome.

Type VI secretion systems in plant‐associated bacteria - Patricia Bernal; María A. Llamas; Alain Filloux (Environmental Microbiology, 2018)
Summary The type VI secretion system (T6SS) is a bacterial nanomachine used to inject effectors into prokaryotic or eukaryotic cells and is thus involved in both host manipulation and interbacterial competition. The T6SS is widespread among Gram‐negative bacteria, mostly within the Proteobacterium Phylum. This secretion system is commonly found in commensal and pathogenic plant‐associated bacteria. Phylogenetic analysis of phytobacterial T6SS clusters shows that they are distributed in the five main clades previously described (group 1–5). The even distribution of the system among commensal and pathogenic phytobacteria suggests that the T6SS provides fitness and colonization advantages in planta and that the role of the T6SS is not restricted to virulence. This manuscript reviews the phylogeny and biological roles of the T6SS in plant‐associated bacteria, highlighting a remarkable diversity both in terms of mechanism and function.

Genome-scale phylogenetic and DNA composition analyses of Antarctic Pseudoalteromonas bacteria reveal inconsistencies in current taxonomic affiliation - Emanuele Bosi; Marco Fondi; Isabel Maida; Elena Perrin; Donatella de Pascale; Maria Luisa Tutino; Ermenegilda Parrilli; Angelina Lo Giudice; Alain Filloux; Renato Fani (Hydrobiologia, 2015)

Diguanylate cyclase D gc P is involved in plant and human P seudomonas spp. infections - Isabel M. Aragon; Daniel Pérez‐Mendoza; Joana A. Moscoso; Emmanuel Faure; Benoit Guery; María‐Trinidad Gallegos; Alain Filloux; Cayo Ramos (Environmental Microbiology, 2015)
Summary The second messenger cyclic di‐ GMP (c‐di‐ GMP ) controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of D gc P (diguanylate cyclase conserved in P seudomonads), whose activity in the olive tree pathogen P seudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgc P gene revealed that D gc P negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P . savastanoi pv. savastanoi and the human opportunistic pathogen P seudomonas aeruginosa . Overexpression of the dgc P gene in P . aeruginosa PAK led to increased exopolysaccharide production and upregulation of the type VI secretion system; in turn, it repressed the type III secretion system, which is a hallmark of chronic infections and persistence for P . aeruginosa . Deletion of the dgc P gene in P . savastanoi pv. savastanoi NCPPB 3335 and P . aeruginosa PAK reduced their virulence in olive plants and in a mouse acute lung injury model respectively. Our results show that diguanylate cyclase D gc P is a conserved P seudomonas protein with a role in virulence, and confirm the existence of common c‐di‐ GMP signalling pathways that are capable of regulating plant and human P seudomonas spp. infections.

The Pseudomonas aeruginosa sensor RetS switches Type III and Type VI secretion via c‐di‐GMP signalling - Joana A. Moscoso; Helga Mikkelsen; Stephan Heeb; Paul Williams; Alain Filloux (Environmental Microbiology, 2012)

The Pseudomonas aeruginosa sensor RetS switches Type III and Type VI secretion via c‐di‐GMP signalling - Joana A. Moscoso; Helga Mikkelsen; Stephan Heeb; Paul Williams; Alain Filloux (Environmental Microbiology, 2011)
Summary Acute bacterial infections are associated with motility and cytotoxicity via the type III secretion system (T3SS), while chronic infections are linked to biofilm formation and reduced virulence. In Pseudomonas aeruginosa , the transition between motility and sessility involves regulatory networks including the RetS/GacS sensors, as well as the second messenger c‐di‐GMP. The RetS/GacS signalling cascade converges on small RNAs, RsmY and RsmZ, which control a range of functions via RsmA. A retS mutation induces biofilm formation, and high levels of c‐di‐GMP produce a similar response. In this study, we connect RetS and c‐di‐GMP pathways by showing that the retS mutant displays high levels of c‐di‐GMP. Furthermore, a retS mutation leads to repression of the T3SS, but also upregulates the type VI secretion system (T6SS), which is associated with chronic infections. Strikingly, production of the T3SS and T6SS can be switched by artificially modulating c‐di‐GMP levels. We show that the diguanylate cyclase WspR is specifically involved in the T3SS/T6SS switch and that RsmY and RsmZ are required for the c‐di‐GMP‐dependent response. These results provide a firm link between the RetS/GacS and the c‐di‐GMP pathways, which coordinate bacterial lifestyles, as well as secretion systems that determine the infection strategy of P. aeruginosa .

Key two‐component regulatory systems that control biofilm formation in Pseudomonas aeruginosa - Helga Mikkelsen; Melissa Sivaneson; Alain Filloux (Environmental Microbiology, 2011)
Summary Biofilm formation in P. aeruginosa is a highly regulated process that proceeds through a number of distinct stages. This development is controlled by a wide range of factors, of which two‐component systems (TCSs) play a key role. In this review, we focus on some of the TCSs that regulate the switch from a motile to a sessile bacterial lifestyle, either via the production of extracellular appendages or by the production of exopolysaccharides. Extracellular appendages, such as flagella, type IV pili and Cup fimbriae are often involved in the initial attachment of bacteria to a surface. In P. aeruginosa , many of these surface structures are regulated by TCSs, and some systems regulate more than one type of appendage. Furthermore, the production of exopolysaccharides, such as Pel and Psl, is required for P. aeruginosa biofilm formation. The regulation of Pel and Psl is post‐transcriptionally repressed by RsmA, the activity of which is controlled by a complex regulatory system involving several sensor kinases and accessory components. Furthermore, the Rsm system is a major control system that inversely regulates factors involved in motility and acute infection on one hand, and factors involved in biofilm formation and chronic infection on the other hand. Finally, a series of TCSs has recently been discovered that regulates biofilm development in a stage‐specific manner. Taken together, these complex regulatory networks allow the bacterium to respond appropriately to diverse environmental stimuli, and increased knowledge of their mechanisms and signals could be of great importance in the design of novel antibacterial strategies.

The PprA–PprB two‐component system activates CupE, the first non‐archetypal Pseudomonas aeruginosa chaperone–usher pathway system assembling fimbriae - Caroline Giraud; Christophe S. Bernard; Virginie Calderon; Liang Yang; Alain Filloux; Søren Molin; Gwennaele Fichant; Christophe Bordi; Sophie de Bentzmann (Environmental Microbiology, 2011)
Summary The opportunistic pathogen Pseudomonas aeruginosa has redundant molecular systems that contribute to its pathogenicity. Those assembling fimbrial structures promote complex organized community lifestyle. We characterized a new 5.8 kb genetic locus, cupE , that includes the conserved usher‐ and chaperone‐encoding genes. This locus, widely conserved in different bacterial species, contains four additional genes encoding non‐archetypal fimbrial subunits. We first evidenced that the cupE gene cluster was specifically expressed in biofilm conditions and was responsible for fibre assembly containing at least CupE1 protein, at the bacterial cell surface. These fimbriae not only played a significant role in the early stages (microcolony and macrocolony formation) but also in shaping 3D mushrooms during P. aeruginosa biofilm development. Using wide‐genome transposon mutagenesis, we identified the PprAB two‐component system (TCS) as a regulator of cupE expression, and further demonstrated the involvement of the PprAB TCS in direct CupE fimbrial assembly activation. Thus, this TCS represents a new regulatory element controlling the transition between planktonic and community lifestyles in P. aeruginosa .

The Pseudomonas aeruginosa patatin‐like protein PlpD is the archetype of a novel Type V secretion system - Richard Salacha; Filip Kovačić; Céline Brochier‐Armanet; Susanne Wilhelm; Jan Tommassen; Alain Filloux; Romé Voulhoux; Sophie Bleves (Environmental Microbiology, 2010)
Summary We discovered a novel secreted protein by Pseudomonas aeruginosa , PlpD, as a member of the bacterial lipolytic enzyme family of patatin‐like proteins (PLPs). PlpD is synthesized as a single molecule consisting of a secreted domain fused to a transporter domain. The N‐terminus of PlpD includes a classical signal peptide followed by the four PLP conserved blocks that account for its lipase activity. The C‐terminus consists of a POTRA (polypeptide transport‐associated) motif preceding a putative 16‐stranded β‐barrel similar to those of TpsB transporters of Type Vb secretion system. We showed that the C‐terminus remains inserted into the outer membrane while the patatin moiety is secreted. The association between a TpsB component and a passenger protein is a unique hybrid organization that we propose to classify as Type Vd. More than 200 PlpD orthologues exist among pathogenic and environmental bacteria, which suggests that bacteria secrete numerous PLPs using this newly defined mechanism.

Distinct oligomeric forms of the Pseudomonas aeruginosa RetS sensor domain modulate accessibility to the ligand binding site - Florence Vincent; Adam Round; Aline Reynaud; Christophe Bordi; Alain Filloux; Yves Bourne (Environmental Microbiology, 2010)
Summary Bacterial two‐component regulatory systems (TCSs) sense environmental stimuli to adapt the lifestyle of microbial populations. For many TCSs the stimulus is a ligand of unknown chemical nature. Pseudomonas aeruginosa utilizes the closely related RetS and LadS sensor kinases to switch between acute and chronic infections. These sensor proteins antagonistically mediate biofilm formation through communication with a central TCS, GacA/GacS. Recently, it was shown that RetS modulates the GacS sensor activity by forming RetS/GacS heterodimers. LadS and RetS are hybrid sensors with a signalling domain consisting of a 7‐transmembrane (7TMR) region and a periplasmic sensor domain (diverse intracellular signalling module extracellular 2, DISMED2). The 2.65 Å resolution crystal structure of RetS DISMED2, called RetSp, reveals three distinct oligomeric states capable of domain swapping. The RetSp structure also displays two putative ligand binding sites. One is equivalent to the analogous site in the structurally‐related carbohydrate binding module (CBM) but the second site is located at a dimer interface. These observations highlight the modular architecture and assembly of the RetSp fold and give clues on how homodimerization of RetS could be modulated upon ligand binding to control formation of a RetS/GacS heterodimer. Modelling the DISMED2 of LadS reveals conservation of only one ligand binding site, suggesting a distinct mechanism underlying the activity of this sensor kinase.